What is visual intimacy? Mapping a complex phenomenon - Lobinger, Katharina; Venema, Rebecca; Tarnutzer, Seraina; Lucchesi, Federico (MedieKultur: Journal of media and communication research, 2021)
Intimacy is a key social goal and the fundamental basis of close social relationships. Current social relationships and the interactions through which they are created and maintained are highly visualised. This visualisation also transforms the way that intimacy is played out. Based on an interdisciplinary literature review, this paper focuses on the concepts of intimacy and visual intimacy, and maps the different roles that visuals can play in intimacy practices. It shows that the content of visuals is not always essential for creating and maintaining intimacy. Practices relating to producing, sharing, and talking about pictures, as well as practices of seeing, also need to be taken into account when discussing the overall concept of visualintimacy.